Case report: First criminal conviction of dog fighting in Brazil: an international network organization - Espejo, Esther; Galante, Alina; Tremori, Tália Missen; Kmetiuk, Louise Bach; Laiola, Matheus Araujo; Biondo, Alexander Welker; Maiorka, Paulo (Frontiers in Veterinary Science, 2024)
Although banned in several countries worldwide, dog fighting has remained a challenge, particularly on criminal investigation, recognition, and prosecution. Besides animal cruelty, dog fighting has been controlled mostly by criminal organizations and accompanied by illegal gambling and drug trafficking. While such competitions may be impaired by advances of legislation on animal welfare and media coverage, international organized crime has been migrating to less regulated and enforced countries. The case herein reported a flagrant dog fighting investigation in an international event involving 27 Pitbull dogs in Mairiporã, located 50 km outside São Paulo City, Brazil. An international network of dog fighting was revealed at the tournament, along with presence of organizers from USA, Mexico, and Peru. Proof was obtained on-site about other similar past and future competitions in other Latin American countries. Dogs were rescued, thoroughly examined for signs of animal cruelty, surveyed for potential diseases, and tested positive for visceral canine leishmaniasis. The process conducted by the state hearing resulted in the highest criminal sentence attributed to animal cruelty in Brazil to date, serving as jurisprudence for future prosecutions. Forensic veterinary medicine was essential in this case as a specialty for police and court assistance, leading to detailed and undeniable report of animal cruelty.